The Purpose of Marriage in Islamic Philosophical Perspective - Hori, Muhammad; Cipta, Eliva Sukma (Journal of Islamicate Studies, 2019)
Marriage is one of the main staple of life's most perfect in the association community. Therefore, philosophically marriage is one of the basic principles of life are most important in the association a perfect society. Marriage is not only just as the road is very precious to organize domestic life and heredity, but can also be seen as a path to the door introduction between a people with the other (male and female), and the introduction it would be a way to deliver aid between one with the other. By using literature study, this article tries to discuss the purpose of marriage in the perspective of Islamic philosophy. Aside from being a strong engagement, marriage is also a contract between two people of different sexes who agree to live together based on religious values.